First‐Generation Bispidine Chelators for 213BiIII Radiopharmaceutical Applications. (2nd July 2020) - Bruchertseifer, Frank; Comba, Peter; Martin, Bodo; Morgenstern, Alfred; Notni, Johannes; Starke, Miriam; Wadepohl, Hubert
Abstract: Hepta‐ and octadentate bispidines (3, 7‐diazabicyclo[3.3.1]nonane, diaza‐adamantane) with acetate, methyl‐pyridine, and methyl‐picolinate pendant groups at the amine donors of the bispidine platform have been prepared and used to investigate Bi III coordination chemistry. Crystal structure and solution spectroscopic data (NMR spectroscopy and mass spectrometry) confirm that the rigid and relatively large bispidine cavity with an axially distorted geometry is well suited for Bi III and in all cases forms nine‐coordinate complexes; this is supported by an established hole size and shape analysis. It follows that nonadentate bispidines probably will be more suited as bifunctional chelators for 213 Bi III ‐based radiopharmaceuticals. However, two isomeric picolinate‐/acetate‐based heptadentate ligands already show very efficient complexation kinetics with 213 Bi III at ambient temperature and kinetic stability that is comparable with the standard ligands used in this field. The experimentally determined hydrophilicities (log D 7.4 values) show that the Bi III complexes reported are relatively hydrophilic and well suited for medicinal applications. We also present a very efficient and relatively accurate method to compute charge distributions and hydrophilicities, and this will help to further optimize the systems reported here. Abstract : Encapsulating the potential of bismuth : Four first‐generation hepta‐ and octadentate bispidines have been prepared for efficient radiolabeling with 213 Bi III, and their ability to form thermodynamically stable and kinetically inert 213 Bi III complexes for targeted radiotherapy. With three of the ligands, radiolabeling is significantly faster than with the "gold standard" DOTA.